Determiner Morphology of Ale - Zelalem Melaku; Samuel Gondere (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
This study was focused on describing the determiner of the Ale language. Therefore, the study followed a descriptive research design and language consultants were selected using purposeful sampling. Then, the linguistic data was collected using interviews, focus group discussions and elicitation. The collected data were analyzed using qualitative methods. The findings show that the demonstrative determiner in Ale is used to show something is near to the speaker/ listener, expressed by husi 'This' for singular and hisi 'These' for plural. Oppositely, to describe some things far from the speaker /listeners are indicated by husa 'That' for singular and hisa 'Those' for plural nouns. Ale's Demonstrative determiners begin with the similar consonant sounds/h-/ and vowel ending. Possessive determiners in Ale show that something belongs to someone. These determiners of Ale are used to describe the belongs of something for someone by inserting before nouns. Quantifiers are also determiners that modify a noun to indicate its quantity. Quantifiers like he tiikisa 'a few', tiikisa 'a little', he kisha' many'. On the other hand, in Ale, quantifiers may describe cardinal and ordinal numbers. Cardinal numbers refer to the number of or quantity of something. Cardinal number quantifiers are; to'on 'one', laki 'two', and izzex 'three'. Ordinal numbers refer to the numeral positions of something. The sample of ordinal quantifiers in Ale is Paayoote' first', lanka' second, and isxxa 'third'.